Interstitial deletion in Xp22.3 is associated with X linked ichthyosis, mental retardation, and epilepsy. Issue 8 (1st August 2000) - Gohlke, B C; Haug, K; Fukami, M; Friedl, W; Noeker, M; Rappold, G A; Haverkamp, F
Abstract : We describe monozygotic male twins with an interstitial deletion of Xp22.3 including the steroid sulphatase gene ( STS ). The twins had X linked ichthyosis, X linked mental retardation, and epilepsy. A locus for X linked mental retardation has been assigned to a region between STS and DXS31 spanning approximately 3 Mb. Recently the locus was further refined to an approximately 1 Mb region between DXS1060 and GS1 . By PCR analysis of flanking STS gene markers in our patients we succeeded in narrowing down the locus to between DXS6837 and GS1 .